2021
DOI: 10.1021/acsami.0c20055
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole-Based Nanorobots Powered by Light and Glucose for Pollutant Degradation in Water

Abstract: Novel photoactive and enzymatically active nanomotors were developed for efficient organic pollutant degradation. The developed preparation route is simple and scalable. Light-absorbing polypyrrole nanoparticles were equipped with a bi-enzyme [glucose oxidase/catalase (GOx/Cat)] system enabling the simultaneous utilization of light and glucose as energy sources for jet-induced nanoparticle movement and active radical production. The GOx utilizes glucose to produce hydrogen peroxide, which is subsequently degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…Photocatalytic degradation has been considered to be an effective and promising method for removing organic dyes from industrial wastewater, where the separation of photogenerated charge carriers and the effective absorption of dye molecules are crucial in the degradation processes . Thanks to their strong ability to capture dye molecules, high surface area, flexible skeleton structure, diversified functions, and intriguing tailorable features, metal–organic frameworks (MOFs) seem to be a promising porous photocatalyst in realizing the efficient degradation of dyes, while MOFs themselves exhibit very poor transmission/separation efficiency of photogenerated charge carriers and limited visible light adsorption ability. Consequently, several efficient inorganic semiconductor/MOF-based heterojunctions, such as TiO 2 @MOF, CdS–NRs/MOF, g-C 3 N 4 /MOF, and BiOBr/MIL-53­(Fe), were developed to significantly improve their photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic degradation has been considered to be an effective and promising method for removing organic dyes from industrial wastewater, where the separation of photogenerated charge carriers and the effective absorption of dye molecules are crucial in the degradation processes . Thanks to their strong ability to capture dye molecules, high surface area, flexible skeleton structure, diversified functions, and intriguing tailorable features, metal–organic frameworks (MOFs) seem to be a promising porous photocatalyst in realizing the efficient degradation of dyes, while MOFs themselves exhibit very poor transmission/separation efficiency of photogenerated charge carriers and limited visible light adsorption ability. Consequently, several efficient inorganic semiconductor/MOF-based heterojunctions, such as TiO 2 @MOF, CdS–NRs/MOF, g-C 3 N 4 /MOF, and BiOBr/MIL-53­(Fe), were developed to significantly improve their photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the replacement of toxic fuel needed for their actuation, scale-down of their dimension to the nanometer scale, and their formulation using scalable synthetic methods for large-scale environmental protection are still challening. 43 Recently, the scientific community has exploited the use of biofriendly biomolecules (e.g., glucose, lactose, and urea) to propel polymeric microtubes or to design new hybrid nanorobots that utilize the light-responsiveness of conductive polymers. For instance, Lyutakov et al reported novel light-absorbing PPy spherical nanoparticles with a bi-enzymatic system glucose oxidase/catalase (GOx/Cat) grafted on their surfaces enabling the concomitant use of light and GOx/Cat as energy sources for jet-induced nanoparticle movement.…”
Section: Polymers As Scaffolds For Hybrid Microrobotsmentioning
confidence: 99%
“…At the same time, reactive oxygen species (ROS) are produced to effectively degrade of organic pollutants in water. 43…”
Section: Polymers As Scaffolds For Hybrid Microrobotsmentioning
confidence: 99%
“…I Schematic representation of the sequent process of nanoparticle preparation, activation, and enzyme immobilization. (Adapted from [ 43 ]. Copyright © 2021 American Chemical Society.)…”
Section: Propulsion Of Micro- and Nanoscale Robotsmentioning
confidence: 99%
“…The swimmers were propelled by bubble propulsion using hydrogen peroxide as a fuel and upon irradiation with UV or visible light. Lyutakov and co-workers have recently reported on glucose-fueled sun light-driven polypyrrole-based nanoswimmers [ 43 ]. Two types of nanorobots were fabricated using a wet chemistry polymerization approach in which pyrrole and 1-(2-carboxyethyl)-pyrrole were used as monomers and mixed in a solution containing iron(III) chloride as oxidant and polyvinyl alcohol.…”
Section: Propulsion Of Micro- and Nanoscale Robotsmentioning
confidence: 99%